Comparison of Priority Areas and Rehabilitation Risk Areas for Post Disaster by K-Means Method - Arif Budiman; Sarjon Defit; Y Yuhandri (Jurnal Sistim Informasi dan Teknologi, 2021)
Among the inhibiting factors for rehabilitation in Padang City is the absence of an assessment of priority areas and rehabilitation risk areas.This study aims to classify these factors into three clusters and the method used in this study was K-Means method.Disaster average data from 2017 until 2019 as well as data on rehabilitation efforts are used in this method. The results achieved indicate that the rehabilitation efforts carried out have not been evenly distributed in the areas prioritized for rehabilitation.This result can also be an input for the Regional Disaster Management Agency of Padang City in mapping and rehabilitating post-disaster areas and evaluating previous rehabilitation efforts.